Development of Hybrid Learning Management System to Improve the Quality of Lectures at Sayyid Ali Rahmatullah State Islamic University Tulungagung - Anam, Khoirul; Asyhar, Beni (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The objective of this article is to develop a learning management system product with the intention of enhancing the quality of hybrid lectures at UIN SATU Tulungagung. The advent of the 21st century has seen the advent of a plethora of novel learning innovations, driven by the rapid advancement of information and communication technology. This represents a potential solution to the various conventional learning issues that have been identified. One such learning innovation product that employs the use of information and communication technology is e-learning. E-learning is a learning model that employs internet technology across a broad spectrum of applications. The objective of these innovations is to enhance the quality of learning. It is therefore important to facilitate the development and utilisation of e-learning. This article is based on research and product development conducted using the ADDIE model. This article presents the development of an e-learning application in the form of a Learning Management System (LMS), which has been designed to accommodate user needs and to allow for the adjustment of roles. The objective of this research is to develop valid, practical, and effective e-learning products. Expert validation indicates an average rating of 92%. The practicality of the application was assessed by users in terms of appearance, material, discussion, and ease of access, with an average rating of 86.39%. The effectiveness of the application was also evaluated based on student learning outcomes, with 82% of students exceeding the target of lecture completeness.